AN EXPLORATION OF CHILD HAWKING IN MAJOR CITIES IN NIGERIA - Saka-Olokungboye, Nurudeen; Victor Akinnigbagbe, Makinde; Toyyib , Olaniyi Musa (African Journal of Social and Behavioural Sciences, 2024)
The prevalence of child hawking is the most pervasive violation of children’s rights in many African countries, particularly in Nigeria. It is a practice that abuses the rights and privileges of the child. Hawking exposes a child to many dangers. This paper explored child hawking in major cities in Nigeria. This theoretical study revealed that illiteracy, poverty, broken homes, unemployment and the death of parents are factors contributing to the menace of child hawking in Nigeria. The paper revealed that hawking poses serious health challenges to a child, with the risk of being sexually molested, in addition to affecting his/her educational development. The authors concluded that more advice should be given on the danger of hawking. Parents should be supported by developing alternative income streams to reduce reliance on child hawking. The paper further recommended genuine empowerment of families through cash transfers and other social security initiatives that can strengthen the finances of parents. The paper further recommended that the government address the problem of poverty, especially in rural areas.